Effects of the psychological stress, fatigue, muscle damage and rest perception in pre-match warm-up of amateur handball players - Estibaliz Romaratezabala Aldasoro; Daniel Castillo Alvira; Josune Rodriguez Negro; Javier Yanci Irigoyen (Federación Extremeña de Balonmano; University of Extremadura, 2019)
The main objective of this study was to analyze the effects of a warm-up protocol on the physical performance, the differentiated perceived exertion (dRPE) and on the perception of being prepared to play a match (PREP) in handball players. Moreover, the influence of the initial level of perception of stress, rest/sleep, fatigue and muscular pain of the players in the physical performance was also analyzed. Twelve senior handball players performed a pre-match standard warm-up for 30 min. At the beginning of the study players' perception of rest/sleep, stress level, level of fatigue, as well as muscle pain was recorded. Before (pretest) and after (post-test) the warm-up all players complete a physical tests battery and declared how prepared they felt to face a match. The results showed that the performed warm-up did not significantly modify the physical performance of the players and there was no significant change either in the value of the perception of being prepared to face the match. However, the players who reported greater stress or worse perception of sleep level at the beginning of the session obtained a worse result in the CODA 505 pretest. Likewise, the players who declared greater stress or greater muscle damage of upper limbs obtained a higher respiratory load perception. Although the pre-game warm-up protocol used in this study did not improve the physical performance or the perception the players had of being prepared to play the match, the results obtained show that the warm-up can be positive to alleviate the adverse effects especially in players who at the beginning of the session perceive higher levels of stress and absence of rest/sleep.